Design, synthesis, calorimetry, and crystallographic analysis of 2-alkylaminoethyl-1,1-bisphosphonates as inhibitors of trypanosoma cruzi farnesyl diphosphate synthase - Aripirala, Srinivas (2012)
Linear 2-alkylaminoethyl-1,1-bisphosphonates are effective agents against proliferation of Trypanosoma cruzi, the etiologic agent of American trypanosomiasis (Chagas disease), exhibiting IC 50 values in the nanomolar range against the parasites. This activity is associated with inhibition at the low nanomolar level of the T. cruzi farnesyl diphosphate synthase (TcFPPS). X-ray structures and thermodynamic data of the complexes TcFPPS with five compounds of this family show that the inhibitors bind to the allylic site of the enzyme, with their alkyl chain occupying the cavity that binds the isoprenoid chain of the substrate. The compounds bind to TcFPPS with unfavorable enthalpy compensated by a favorable entropy that results from a delicate balance between two opposing effects: the loss of conformational entropy due to freezing of single bond rotations and the favorable burial of the hydrophobic alkyl chains. The data suggest that introduction of strategically placed double bonds and methyl branches should increase affinity substantially.